2021
DOI: 10.1021/jacs.1c03026
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Entangled Triplet Acyl–Alkyl Radical Pairs in Crystals of Photostable Diphenylmethyl Adamantyl Ketones

Abstract: Radical pairs generated in crystalline solids by bond cleavage reactions of triplet ketones offer the unique opportunity to explore a frontier of spin dynamics where rigid radicals are highly entangled as the result of short interradical distances, large singlet−triplet energy gaps (ΔE ST ), and limited spin−lattice relaxation mechanisms. Here we report the pulsed laser generation and detection of strongly entangled triplet acyl−alkyl radical pairs generated in nanocrystalline suspensions of 1,1-diphenylmethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…If the resulting alkyl radical recombines with the second alkoxy radical, they form an ester. The overall proposed mechanism is analogous to a photochemical process recently characterized in crystalline solids, where a triplet radical pair produced by laser photolysis may undergo CO loss, followed by ISC and recombination …”
Section: Introductionmentioning
confidence: 84%
“…If the resulting alkyl radical recombines with the second alkoxy radical, they form an ester. The overall proposed mechanism is analogous to a photochemical process recently characterized in crystalline solids, where a triplet radical pair produced by laser photolysis may undergo CO loss, followed by ISC and recombination …”
Section: Introductionmentioning
confidence: 84%
“…Crystalline solids offer opportunities to study previously unchartered regions of chemical dynamics 1,2 and to carry out highly selective reactions. 3,4 Our recent report on the reversible formation of triplet acyl−alkyl radical pairs generated by photochemical excitation of nanocrystalline diphenylmethyladamantyl ketones (Figure 1a, R = adamantyl, R 1 = R 2 = Ph, R 3 = H) 5 suggested a new platform for the repeated generation of qubit pairs with potential applications in quantum information science. 6−8 We confirmed that triplet radical pairs generated by the cleavage of a single bond, and forced to remain nearly static within a bond distance, are strongly correlated as they lack efficient mechanisms for intersystem crossing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Using laser flash photolysis with nanocrystalline samples suspended in water, 10 we showed that triplet acyladamantyl-diphenylmethyl radical pairs ( 3 RP-A) have lifetimes in the range of ca. 50−60 μs, 5 which are one to four orders magnitude longer than analogous acyl−alkyl biradicals held close together by short alkyl chains in solution. 11−13 Recognizing that longer lifetimes will make it possible to execute multiple logical operations by quantum spin-state manipulation, 14 we sought to investigate a series of triphenylmethyl-substituted ketones that may lead to longerlived triplet pairs by taking advantage of the persistent nature of the triphenylmethyl (trityl) radical (Figure 1a, R 1 = R 2 = R 3 = Ph).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations